X-ray radioscopy validation of a polyol functionalized with graphene oxide for producing rigid polyurethane foams with improved cellular structures. (September 2019) - Santiago-Calvo, Mercedes; Pérez-Tamarit, Saúl; Cimavilla-Román, Paula; Blasco, Victoria; Ruiz, Carolina; París, Rodrigo; Villafañe, Fernando; Rodríguez-Pérez, Miguel Ángel
Graphical abstract: Highlights: Polyols functionalized with GO (GO-f) and filled with GO (GO-d) are used. The foaming of RPU foams with GO-f or GO-d is followed by X-Ray radioscopy. The cellular structure of RPU foams are improved by incorporation of GO-f. GO-f offers better results than GO-d. Abstract: Fillers can be dispersed in polyurethane (PU) components to produce PU foams with improved properties by different methods. Herein, graphene oxide (GO) is chemically linked to polyol chains in order to suppress fillers agglomeration. Then the foaming behaviour of rigid polyurethane (RPU) foams from polyols functionalized with GO (GO-f) is compared with the one of RPU foams containing GO dispersed in the polyol (GO-d) by high shear mixing. Relative density, cell size, and cell nucleation density of the RPU foam nanocomposites are monitored during the foaming process by using X-ray radioscopy. The results obtained demonstrate that the use of polyol functionalized with GO-f offers a high improvement of the cellular structure and also makes the results more reproducible.